Mating system and two types of gametogenesis in the fresh water diatom Ulnaria ulna (Bacillariophyta) - Podunay, Yu.A.; Davidovich, O.I.; Davidovich, N.A. (Альгология, 2014)
Sexual reproduction and mating system of the freshwater diatom Ulnaria ulna (Nitzsch) Compère were studied by using clonal cultures. Mating system of the species involves homo- and heterothallic modes of reproduction; and both male and female clones were capable of homothallic reproduction. Two types of gametogenesis corresponding to two mating types were investigated. Analysis of the crossing table, gamete morphology, and sex distribution in the progeny resulted from intraclonal reproduction provided evidences that anisogamy and two mating types were determined in U. ulna genetically; male and female clones were hetero- and homogametic correspondently. Specific active movement of male gametes caused by the formation and retraction of pseudopodia-like structures on the gamete surface was described. The absence of reproductive isolation between clones gathered from geographically distant populations suggests continuity and broad distribution of the species. Вивчені статеве розмноження і система схрещування прісноводної діатомеї Ulnaria ulna (Nitzsch) Compère з використанням клонових культур. Система схрещування виду складається з гомо- та гетероталічних способів відтворення, причому як чоловічі, так і жіночі клони здатні відтворюватися гомоталічно. Вивчені два типи гаметогенезу, які відповідали розділенню клонів за статевою ознакою. Аналіз таблиці схрещування, морфології гамет і розподілу статі у потомстві, отриманому при внутрішньоклоновому відтворенні, служать доказом того, що анізогамія і поділ на дві статі зумовлені у U. ulna генетично; чоловічий і жіночий клони є гетеро- і гомогаметними відповідно. Описано також активний рух чоловічих статевих клітин, викликаний утворенням і втягуванням на поверхні гамет структур, подібних псевдоподіям. Відсутність репродуктивної ізоляції між клонами, зібраними з географічно віддалених популяцій, передбачає цілісність та широке розповсюджeння виду.